Analysis of Long Non-Coding RNA and mRNA Expression Profiling in Immature and Mature Bovine (Bos taurus) Testes - Gao, Yuan; Li, Shipeng; Lai, Zhenyu; Zhou, Zihui; Wu, Fei; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong; Dang, Ruihua (Frontiers in Genetics, 2019)
Testis development and spermatogenesis are strictly regulated by numbers of genes and non-coding genes. However, Long non-coding RNAs (lncRNAs) as key regulators in multitudinous biological processes have not been systematically identified in bovine testes during sexual maturation. In this study, we comprehensively analyzed lncRNA and mRNA expression profiling of six bovine testes at 3d after birth and 13 months by RNA sequencing. 23,735 lncRNAs and 22,118 mRNAs were identified, in which, 540 lncRNAs (P-value < 0.05) and 3,525 mRNAs (P-adjust < 0.05) were significantly differentially expressed (DE) between two stages. Correspondingly, the results of RT-qPCR analysis showed well correlation with the transcriptome data. Moreover, GO and KEGG enrichment analyses showed that DE genes and target genes of DE lncRNAs were enriched in spermatogenesis. Furthermore, we constructed lncRNA-gene interaction networks, consequently, 15 DE lncRNAs and 12 cis-target genes were involved. The target genes (SPATA16, TCF21, ZPBP, PACRG, ATP8B3, COMP, ACE and OSBP2) were found that association with bovine sexual maturation. In addition, the expression of lncRNAs and cis-target genes were detected in bovine Leydig cells, Sertoli cell, and spermatogonia. Our study identified and analyzed lncRNAs and mRNAs in testis tissues, suggesting that lncRNAs may regulate testis development and spermatogenesis. Our findings provided new insights for further investigation of biological function in bovine lncRNA.